2012
DOI: 10.1103/physreva.86.063817
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ghost imaging with averaged speckle patterns

Abstract: We present theoretical and experimental results showing that a thermal ghost imaging system can produce images of high quality even when it uses detectors so slow that they respond only to intensity-averaged (that is, "blurred") speckle patterns, as long as the collected signal variation is predominantly caused by the random fluctuation of the incident speckle field rather than other noise sources. In our experimental study, we show that the quality of the ghost image is not degraded when as many as 25 speckle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 25 publications
(43 reference statements)
1
36
0
Order By: Relevance
“…With the model introduced by Chan et al [16,17] and Brida et al [15], an analysis of image quality of transmissive ghost imaging with averaged speckle patterns was presented by Zerom et al [18]. Here we discuss the CNR of RGI following this model.…”
Section: Theoretical Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…With the model introduced by Chan et al [16,17] and Brida et al [15], an analysis of image quality of transmissive ghost imaging with averaged speckle patterns was presented by Zerom et al [18]. Here we discuss the CNR of RGI following this model.…”
Section: Theoretical Analysismentioning
confidence: 94%
“…The ghost image of the object can be reconstructed by correlating the bucket signal with the intensity distribution of the incident speckle pattern projected onto the object, averaging over many measurements. The second-order correlation of RGI can be expressed as [16][17][18] …”
Section: Theoretical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The first demonstration of ghost imaging (GI) [1,2] utilized biphoton pairs which were produced by spontaneous parametric down conversion in a nonlinear crystal, hence the phenomenon was interpreted as the result of quantum entanglement of the photon pairs [3]. Subsequently, further theoretical and experimental work showed that GI is also achievable with pseudo-thermal [4][5][6][7][8][9][10] as well as true thermal light [11,12] and can be explained with a classical statistical model [13,14].…”
Section: Introductionmentioning
confidence: 99%